Course of uveitis in children with juvenile idiopathic arthritis (JIA): Five years follow-up data from a prospective multicenter Inception Cohort of Newly diagnosed patients with JIA (ICON-JIA) study - Karoline Baquet-Walscheid; Kirsten Minden; Martina Niewerth; Frank Dressler; Ivan Foeldvari; Dirk Foell; Johannes-Peter Haas; Gerd Horneff; Anton Hospach; Tilmann Kallinich; Jasmin Kümmerle-Deschner; Kirsten Mönkemöller; et al. (Arthritis Research & Therapy)
Abstract Background Juvenile idiopathic arthritis-associated uveitis (JIAU) typically takes a chronic course, frequently leading to ocular complications and often requiring long-term treatment. The present study assesses the 5-years outcome of JIAU by analyzing data from a prospective study initiated in 2010. Methods Data from 75 patients with onset of uveitis after study enrollment, and with a documentation at 5-years follow-up (5yFU) were available for analysis of uveitis characteristics, frequency and predictors of „inactivity on medication “ (defined as inactive uveitis for ≥ 6 months) and „inactivity off medication “ (defined as inactive uveitis for ≥ 6 months off medication). Results At the 5yFU, visual acuity remained good in the majority of eyes (LogMAR < 0.1 in 65.5%; mean LogMAR 0.11 ± 0.31), ocular surgery was required in only 5% of patients, although complications occurred in 46.7% of patients until the 5yFU. Uveitis was inactive in 85.3% of patients, with 77.3% still receiving disease-modifying antirheumatic drugs (DMARDs). Until 5yFU, 82.7% of patients experienced ≥ one episode of „inactivity on medication “ (30.7% once, 37.3% twice, 14.7% three or more times), and 17.3% ≥ one episode of „inactivity off medication “, respectively. Both „inactivity on medication “ as well as „inactivity off medication “ were associated with lower JIA disease activity (cJADAS10; ESR), and with an increased quality of life. Conclusions Despite intensified DMARD treatment, almost half of the children experience JIAU-related ocular complications after 5 years of disease; however, visual acuity mostly remains good. Uveitis inactivity can be achieved frequently, but is often limited in duration. Lower JIA activity appears to correlate with uveitis inactivity on and off medication.